Antigens of aspergillus fumigatus. 1. Purification of a cytoplasmic antigen reactive with sera of patients with aspergillus-related disease. - Calvanico, N J (1981)
An antigen has been purified from the mycelial cell sap of Aspergillus fumigatus (strain 507). The same component appears to be present in the extracellular phase (culture filtrate) in a partially degraded form. The cell sap protein has a structure composed of four polypeptides of 45,000 daltons linked through disulphide bonds. The isoelectric point (5.2-5.6) and carbohydrate content (12.5% neutral hexose) indicate that this protein is an acidic glycoprotein. It shows reactions with 75% of sera from patients with aspergilloma and allergic bronchopulmonary aspergillosis and is not reactive with sera from normal individuals of patients with other fungal diseases. It also appears to be a component of other A. fumigatus strains.